2018
DOI: 10.3991/ijet.v13i10.9461
|View full text |Cite
|
Sign up to set email alerts
|

Score Prediction Model of MOOCs Learners Based on Neural Network

Abstract: Through analyzing the behavior data of MOOCs learners, a MOOCs learner's score prediction model is constructed based on clustering algorithm and neural network in this paper. By using this model, we can find out the neglected information and hidden learning rules in the MOOCs learning process. The model can provide personalized guidance for each user and improve learning efficiency. The model can provide personalized service to help learners form personalized learn-ing strategies, and it also can alert learner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…The main components of the brain are cells, as are other parts of the body. Brain cells have the ability to remember, think and apply the experiences they have experienced (Zhang, and Jiang, 2018). An ANN generally consists of three layers, namely the input layer, hidden layer, and output layer.…”
Section: Methodsmentioning
confidence: 99%
“…The main components of the brain are cells, as are other parts of the body. Brain cells have the ability to remember, think and apply the experiences they have experienced (Zhang, and Jiang, 2018). An ANN generally consists of three layers, namely the input layer, hidden layer, and output layer.…”
Section: Methodsmentioning
confidence: 99%
“…However, the maximum consumption in a single month is relatively high, and the number of consumptions is also relatively small. Such students eat irregularly in the cafeteria and usually like to eat out of school or order takeaways (5) The average monthly consumption of type 5 students is relatively low, the number of times is relatively small, and the maximum consumption is not high. Such students do not consume frequently in the cafeteria and are more likely to eat outside of school and consume more outside of school.…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
“…Reference [4] uses an improved recurrent neural network to simulate the student's answering process according to the student's answer records and the content of each exercise to predict the student's future performance. Based on MOOCs learner behavior data, reference [5] established a prediction model based on clustering algorithm and neural network to mine the learning rules in the learning process. The predicted results can provide personalized guidance for each learner.…”
Section: Introductionmentioning
confidence: 99%
“…Arsad et al used neural networks to predict the CGPA at the 8 th semester of undergraduate students based on their grade points in fundamental courses [23]. Most recently, the study presented high accuracy results of performance prediction using neural networks in massive online course learner's data [24]. The study, which reviewed research works on performance prediction reported that neural networks presented the highest prediction accuracy compared with other data-mining techniques [7].…”
Section: Related Workmentioning
confidence: 99%